POLA KOMUNIKASI PEMASARAN DINAS PARIWISATA DAN KEBUDAYAAN DALAM MEMBANGUN MEREK DESTINASI WISATA BAHARI DI KOTA PADANG - Mardhiyyah Mardhiyyah (Universitas Mercu Buana, 2020)
The research entitled Marketing Communication Pattern of the Tourism and Culture Office in Building a Maritime Tourism Destination Brand in Padang City intends to find out the patterns and marketing communication strategies carried out by the Tourism and Culture Office in Padang City in building their Maritime Tourism Destination Brand. This is motivated by the need for the Government Office, especially regarding tourism to be able to do marketing and promotion so that tourists who visit continue to increase. Coupled with an increase in the tourism sector is one part of President Joko Widodo's nawacita that must be realized. The city of Padang has amazing marine tourism destinations. For example, like Padang Beach, Air Manis Beach, Pasir Jambak Beach, Nirwana Beach and Caroline Beach..